2016
DOI: 10.1016/j.bjan.2013.06.025
|View full text |Cite
|
Sign up to set email alerts
|

O impacto da analgesia controlada pelos pacientes submetidos a cirurgias ortopédicas

Abstract: Como citar este artigo: Dias AS, et al. O impacto da analgesia controlada pelos pacientes submetidos a cirurgias ortopé-dicas. Rev Bras Anestesiol. 2014. http://dx. ResumoIntrodução: As disfunções musculoesqueléticas, comuns atualmente, têm sido cada vez mais tratadas cirurgicamente e a dor é pode ser um fator limitante na reabilitação pós-operatória. Justificativa: A analgesia controlada pelo paciente (PCA) controla a dor, porém seus efeitos adversos podem interferir no processo de reabilitação e alta dos pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
1
0
1
Order By: Relevance
“…In this sense, many investigations in different contexts have been carried out to establish possible preventive measures. 1 A recent publication by the World Health Organization revealed that 80% of the world's population has had at least one episode of back pain, highlighting the importance of properly managing this clinical condition. 2 The literature shows that between 10% and 20% of cases of low back pain can become chronic, requiring some kind of long-term intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, many investigations in different contexts have been carried out to establish possible preventive measures. 1 A recent publication by the World Health Organization revealed that 80% of the world's population has had at least one episode of back pain, highlighting the importance of properly managing this clinical condition. 2 The literature shows that between 10% and 20% of cases of low back pain can become chronic, requiring some kind of long-term intervention.…”
Section: Introductionmentioning
confidence: 99%
“…A dor é um dos principais fatores que limitam a deambulação e causam o aumento do risco de tromboembolismo pela imobilidade, além de alterações metabólicas que afetam vários outros sistemas 17,18 . Por conta disso, torna-se fundamental o manejo individualizado da dor, com o uso de técnicas analgésicas adequadas como a crioterapia, utilizada em nosso protocolo institucional 19,20 . Além disso, a reabilitação precoce, com foco em acelerar a recuperação pós-operatória, pode reduzir o tempo de internação hospitalar e o retorno às atividades de vida diária 21,22 .…”
unclassified